Large-scale preparation of g-C3N4 nanotube array with high nitrogen ratio and preparation method thereof
Through urea and hydroxylamine sulfate as nitrogen sources, using hydrothermal reaction and supramolecular self-assembly technology, a high nitrogen ratio g-C3N4 nanotube array was prepared, which solved the problems of complex preparation process and low yield in the existing technology, and achieved efficient and simple nanotube array preparation, expanding its application potential in multiple fields.
Patent Information
- Application Number
- CN202411712772.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The method for preparing g-C3N4 nanotube arrays in the prior art has problems such as complex operation, dangerousness, low product purity, time-consuming and low yield, and traditional template-assisted synthesis has problems such as pollution and high economic costs in the template removal process.
Urea and hydroxylamine sulfate are used as nitrogen sources, and a high nitrogen ratio g-C3N4 nanotube array is formed through hydrothermal reaction and supramolecular self-assembly technology, which avoids the use of templates, simplifies the preparation process, and improves yield and purity.
Large-scale preparation of high-nitrogen ratio g-C3N4 nanotube arrays has been achieved, with high specific surface area, low band gap and high nitrogen content, expanding its application prospects in the fields of photocatalysis, electrocatalysis, adsorption, biosensing and biomedicine.
Smart Images

Figure CN119528095A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor nanomaterial preparation, and more specifically, relates to a method for large-scale preparation of high nitrogen ratio gC 3 N 4 Nanotube array and preparation method thereof, obtained high nitrogen ratio gC 3 N 4 Nanotube arrays are suitable for applications in photocatalysis, electrocatalysis, adsorption, biosensing, biomedicine and other fields. Background Art
[0002] Graphitic carbon nitride (gC 3 N 4 As a green, non-toxic, non-metallic organic polymer semiconductor with a suitable band gap (2.7 eV), it has been widely studied in biomedical applications, sensor devices, and photoelectrocatalysis due to its excellent high temperature resistance, good chemical stability, and unique two-dimensional structure. 3 N 4 It is a two-dimensional layered structure formed by stacking graphene atoms through covalent bonds between C and N, in which the tri-s-triazine unit is gC 3 N 4 The most stable unit of existence, with band tunability. However, the traditional bulk gC 3 N 4 The quantum confinement effect, low specific surface area and limited active sites of nanomaterials largely limit the high charge carrier efficiency and hinder their further practical applications. 3 N 4 Nanotube arrays are widely praised in the fields of photocatalysis, electrocatalysis, adsorption, biosensing, biomedicine, etc. for their unique hierarchical structure, close interface contact, high electron transfer, easy mass transfer, large specific surface area and a large number of active sites, which show excellent test performance. Therefore, large-scale preparation of gC 3 N 4 Nanotube arrays have become the focus of attention.
[0003] So far, the gC 3 N 4 Nanotube arrays are mainly synthesized by hard template technology. This method is considered to be the use of specific templates to control morphology, porosity, specific surface area and size to prepare gC 3 N 4Nanotube array materials. Specifically, porous anodic aluminum oxide (AAO) templates are used as substrates and are constructed through three steps of precursor infiltration, precursor structure transformation, and template removal. The product structure obtained by this method relies on the inherent structure of the template and is therefore relatively easy to control. However, during the template removal process, it is susceptible to the dangers of etchants (such as NaOH, HF, etc.), is time-consuming, and has low yields. The preparation process will result in residual template or etchant elements (such as Al, Na, F, etc.), further affecting the prepared gC 3 N 4 The purity of the nanotube array. From a cost perspective, disposable AAO templates are not economical. 3 N 4 The problems existing in the preparation process of nanotube arrays require a preparation method with simple operation and preparation process, mild reaction and high yield. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the object of the present invention is to provide a large-scale preparation of high nitrogen ratio gC 3 N 4 Nanotube array and preparation method thereof, wherein the reaction mechanism and reaction process design of the preparation method are improved, urea and hydroxylamine sulfate are used as nitrogen sources, and gC can be obtained without the aid of rigid template induction auxiliary synthesis 3 N 4 Nanotube array material, prepared gC 3 N 4 The nanotube array material is a single-phase material with the characteristics of high nitrogen ratio (i.e., high nitrogen content), simple preparation method, mild reaction conditions, easy operation, and cheap and readily available raw materials, which can solve the shortcomings and deficiencies of the prior art, such as complex operation process, danger, low product purity, time-consuming and low yield. In addition, the gC prepared by the present invention 3 N 4 In addition to the characteristics of high nitrogen content, nanotube array nanomaterials also have the characteristics of large specific surface area and low band gap, which can expand gC 3 N 4 Application of materials in photocatalysis, electrocatalysis, adsorption, biosensing and biomedicine.
[0005] To achieve the above object, according to one aspect of the present invention, a high nitrogen ratio gC 3 N 4 The method for preparing a nanotube array comprises the following steps:
[0006] (1) uniformly dissolving urea in water to obtain a single nitrogen source mixed solution;
[0007] (2) adding hydroxylamine sulfate to the single nitrogen source mixed solution and uniformly dissolving it to obtain a multi-nitrogen source mixed solution;
[0008] (3) adding melamine to the multi-nitrogen source mixed solution, mixing and dispersing the mixture uniformly to obtain a dispersion of a multi-nitrogen source mixed melamine system;
[0009] (4) subjecting the dispersion of the multi-nitrogen source mixed melamine system to a hydrothermal reaction, wherein the hydrothermal temperature of the hydrothermal reaction is 120° C.-200° C., and the reaction time is 12 h-48 h; after the reaction is completed, collecting the reaction product, and washing and drying the reaction product to obtain a multi-nitrogen source doped melamine precursor powder; the multi-nitrogen source doped melamine precursor powder has a nano columnar array structure;
[0010] (5) The multi-nitrogen source doped melamine precursor powder is tightly wrapped with aluminum foil and then calcined in an air atmosphere to obtain gC with a high nitrogen ratio. 3 N 4 Nanotube array nanomaterials.
[0011] As a further preferred embodiment of the present invention, the usage ratio of the urea, the hydroxylamine sulfate and the melamine satisfies the mass ratio of (0.74g-4.28g):(1g-6g):(0.5g-3g).
[0012] As a further preferred embodiment of the present invention, in the multi-nitrogen source mixed solution, the ratio of the mass of the hydroxylamine sulfate to the volume of the solvent water is (1 / 30) to 0.06 g / mL.
[0013] As a further preference of the present invention, in step (3), the dispersion is carried out by ultrasonic treatment, and the ultrasonic treatment time is 20-60 min.
[0014] As a further preferred embodiment of the present invention, in step (4), the cleaning is performed by alternating ultrapure water and ethanol for multiple times; the drying temperature used in the drying is 50° C.-80° C., and the drying time is 20 h-30 h.
[0015] As a further preferred embodiment of the present invention, in step (4), the cleaning is performed by alternating ultrapure water and ethanol for a total of 7 times, and ultrapure water is used for the last cleaning.
[0016] As a further preferred embodiment of the present invention, in step (5), the calcination temperature used is 500°C-600°C, the heating rate is 1°C / min-10°C / min, and the holding time is 3h-5h.
[0017] According to another aspect of the present invention, the present invention provides a high nitrogen ratio gC 3 N 4Nanotube arrays.
[0018] As a further preferred embodiment of the present invention, the high nitrogen ratio gC 3 N 4 The mass percentage of nitrogen in the nanotube array is greater than 44.81%, preferably greater than 52.76%.
[0019] As a further preferred embodiment of the present invention, the high nitrogen ratio gC 3 N 4 In the nanotube array, the elemental mass percentages of carbon, nitrogen, and oxygen are 17.02%, 76.59%, and 6.39%, respectively.
[0020] Through the above technical scheme conceived by the present invention, compared with the prior art, the preparation method of the present invention uses melamine as a raw material, urea as a nitrogen source, and hydroxylamine sulfate as a catalytic nitrogen source, and controls the morphology of melamine by a hydrothermal method, so that the melamine is transformed from an irregular granular structure into a modified melamine precursor with a directional arrangement and a nano-columnar array structure (i.e., a multi-nitrogen source-doped melamine precursor); and the modified precursor is calcined in air to obtain a high-nitrogen-content doped, directional-arranged three-dimensional gC 3 N 4 Nanotube array nanomaterials.
[0021] Moreover, unlike the bulk phase gC 3 N 4 The nitrogen content is 44.81%, and the single nitrogen source doping gC 3 N 4 The nitrogen content of the nanotubes is 52.76%. 3 N 4 The nanotube array has a nitrogen content of 76.59%, which is characterized by a high nitrogen ratio, and also increases the specific surface area and reduces the electronic energy band gap (as described later). Fig.14 , Fig.15 , Fig.16 and Fig.17 shown).
[0022] In addition, compared with the gC synthesized by the hard template method in the prior art 3 N 4 Nanotube arrays, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art, for the traditional template separation process, the product structure is easy to be destroyed, the template elements or etching elements are easy to introduce to contaminate the product, and the disposable template is not cost-effective, the present invention is based on the supramolecular self-assembly reaction of gC 3 N 4The preparation method of the nanotube array has a more fluffy spacing between nanotubes in the array structure from a microscopic perspective, which can effectively provide a larger specific surface area and electron transmission capacity, and does not contain the presence of impurity elements to ensure the purity of the product. The nitrogen element introduced into the product by the precursor molecule is beneficial to improving the microstructure and electronic structure of the product, effectively solving the shortcomings and deficiencies of the prior art such as cumbersome operation process, danger, easy contamination and low yield.
[0023] Specifically, the present invention can achieve the following beneficial effects:
[0024] (1) The preparation method of the present invention uses melamine as a raw material, urea as a nitrogen source, and hydroxylamine sulfate as a catalytic nitrogen source. First, a hydrothermal reaction is used to promote supramolecular self-assembly to form a three-dimensional nanocolumn array precursor (i.e., a multi-nitrogen source-doped melamine precursor). During the hydrothermal process, urea molecules and hydroxylamine sulfate molecules promote the conversion of irregularly structured granular melamine into a nanocolumn structure based on the supramolecular assembly reaction. Subsequently, urea molecules and hydroxylamine sulfate molecules self-assemble with melamine molecules in large quantities through hydrogen bonds to form a modified melamine precursor with a directional arrangement and a nanocolumn array structure. Then, the modified intermediate with a specific structure is calcined in an air atmosphere to cause the nanocolumn to peel off and gradually form a nanotube structure. At the same time, the high-strength hydrogen bonds further fix the stability of the array structure, thereby forming a gC with a high nitrogen ratio. 3 N 4 Nanotube array nanomaterials.
[0025] As exemplified in Example 1 below, gC 3 N 4 Nanotube array, the array structure is highly ordered, the nanotubes are tightly bound, the average yield is about 50%, the nanotube array length (i.e., tube length) is >30μm, the average tube diameter of the nanotube array is about 376.23nm, and the element contents of carbon, nitrogen, and oxygen are 17.02%, 76.59%, and 6.39%, respectively.
[0026] (2) Considering the different solubilities of urea, hydroxylamine sulfate, and melamine in water, the method of the present invention first dissolves urea in water, then adds hydroxylamine sulfate, and finally adds melamine, so that the melamine molecules can fully contact the nitrogen source, so that the subsequent hydrothermal reaction can be completed. The present invention controls the morphology of the melamine precursor for the first time, and further controls the reaction characteristics during the hydrothermal and calcination process by adding different nitrogen sources, thereby further controlling the gC with a high nitrogen ratio produced after calcination. 3 N 4 Nanotube array nanomaterials. The nanotubes have smooth surfaces and obvious internal channels, indicating that the bulk phase gC can be effectively regulated by continuous doping with nitrogen sources. 3 N 4The microstructure of nanomaterials further enhances their application prospects in the fields of light, electrocatalysis or electrochemistry, adsorption and biomedicine. At the same time, the highly ordered nanotube array structure also enhances the structural stability during the application process, which can further effectively improve the stability of the test in actual application.
[0027] (3) The hydrothermal supramolecular self-assembly coupled high-temperature pyrolysis method used in the present invention is superior to the traditional template-assisted synthesis of gC 3 N 4 The preparation method of nanotube array material has no special requirements for equipment and has extremely high yield, simple operation, short time consumption, low cost, green and environmental protection, safety and reliability, and is conducive to large-scale industrial production.
[0028] (4) gC with high nitrogen ratio prepared by the present invention 3 N 4 Nanotube array nanomaterials and bulk gC 3 N 4 Compared with other materials, it has a higher specific surface area, high nitrogen content, better light absorption range, etc., which further promotes its wide application in multi-field research.
[0029] (5) The preparation method of the present invention abandons the traditional template-assisted induction synthesis concept, selects cheap and easily available melamine as the raw material, optimizes the hydrothermal temperature and time based on the self-assembly reaction of the precursor molecules in the hydrothermal process, and selects a suitable nitrogen source precursor. Specifically, urea and hydroxylamine sulfate molecules are used to couple the melamine precursor molecules through a high degree of hydrogen bonding to dominate the chemical structure, and an infinitely repeating unit of the monomer molecular structure is constructed through a multi-combination design. After the hydrothermal reaction is completed, gC can be obtained by calcination. 3 N 4 Nanotube arrays, due to their three-dimensional ordered and regular structural characteristics, highly exposed active sites and high nitrogen content doping, will cause changes in the electronic structure of the material, thereby expanding gC 3 N 4 The material is applied in the fields of photocatalysis, electrocatalysis, adsorption, biosensor, biomedicine, etc. The method of the present invention can preferably control the mass ratio of urea, hydroxylamine sulfate and melamine to (0.74g-4.28g): (1g-6g): (0.5g-3g), and can particularly preferably control the mass ratio to 1.47:2:1. After hydrothermal treatment and calcination treatment, gC with good performance and high nitrogen ratio can be obtained. 3 N 4 Nanotube array nanomaterials.
[0030] In summary, the preparation method of the present invention is simple, energy-saving, green, safe, and has cheap raw materials. 3 N 4The nanotube array structure is orderly and stable, and also has the characteristics of high nitrogen ratio, showing similarity to the bulk phase gC 3 N 4 Different electronic band structure characteristics can expand gC 3 N 4 Application of materials in photocatalysis, electrocatalysis, adsorption, biosensing, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope (SEM) image of the melamine used in Example 1.
[0032] Figure 2 This is the SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 1.
[0033] Figure 3 The X-ray diffraction (XRD) diagram of the multi-nitrogen source doped melamine precursor and melamine prepared in Example 1.
[0034] Figure 4 The bulk phase gC prepared by one-step calcination of melamine in Comparative Example 1 3 N 4 SEM image of .
[0035] Figure 5 The high nitrogen ratio gC prepared in Example 1 3 N 4 SEM image of nanotube array.
[0036] Figure 6 The high nitrogen ratio gC prepared in Example 1 3 N 4 Diameter distribution of nanotube arrays.
[0037] Figure 7 The bulk phase gC prepared by one-step calcination of melamine in Comparative Example 1 3 N 4 Energy dispersive spectrum (EDS) element distribution diagram (the percentages in the figure are the mass percentages of the corresponding elements).
[0038] Figure 8 The single nitrogen source doped gC prepared in Comparative Example 2 3 N 4 EDS element distribution diagram of nanotubes (the percentages in the figure are the mass percentages of the corresponding elements).
[0039] Fig. 9 The high nitrogen ratio gC prepared in Example 1 3 N 4 EDS element distribution diagram of the nanotube array (the percentages in the figure are the mass percentages of the corresponding elements).
[0040] Fig.10 The high nitrogen ratio gC prepared in Example 1 3 N 4 Transmission electron microscopy (TEM) image of a nanotube array.
[0041] Fig.11 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC obtained in Comparative Example 2 3 N 4 XRD comparison of nanotubes.
[0042] Fig.12 The high nitrogen ratio gC prepared in Example 1 3 N 4 Yield plot of nanotube arrays.
[0043] Fig.13 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC obtained in Comparative Example 2 3 N 4 Comparison of Fourier transform infrared (FT-IR) spectra of nanotubes.
[0044] Fig.14 The bulk phase gC prepared by one-step calcination of melamine in Comparative Example 1 3 N 4 Specific surface area test (BET) diagram.
[0045] Fig.15 The single nitrogen source doped gC prepared in Comparative Example 2 3 N 4 Nanotube specific surface area test (BET) diagram.
[0046] Fig.16 The high nitrogen ratio gC prepared in Example 1 3 N 4 BET plot of nanotube arrays.
[0047] Fig.17 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array (corresponding to the blue legend) and bulk gC obtained in Comparative Example 1 3 N 4 (corresponding to the black legend) and gC obtained in Comparative Example 2 3 N4 Ultraviolet-visible spectrophotometry (UV-Vis) comparison of nanotubes (corresponding to the red legend).
[0048] Fig.18 This is the SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 2.
[0049] Fig.19 The high nitrogen ratio gC prepared in Example 2 3 N 4 SEM image of nanotube array.
[0050] Fig. 20 This is the SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 3.
[0051] Fig.21 The high nitrogen ratio gC prepared in Example 3 3 N 4 SEM image of nanotube array.
[0052] Fig. 22 This is the SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 4.
[0053] Fig.23 The high nitrogen ratio gC prepared in Example 4 3 N 4 SEM image of nanotube array.
[0054] Fig.24 This is the SEM image of the single nitrogen source doped melamine precursor prepared in Comparative Example 2.
[0055] Fig.25 gC prepared in Comparative Example 2 3 N 4 SEM image of nanotubes.
[0056] Fig.26 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC prepared in Comparative Example 2 3 N 4 Comparison of cyclic voltammetry (CV) of nanotubes.
[0057] Fig. 27 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC prepared in Comparative Example 2 3 N4 Comparison of electrochemical impedance spectroscopy (EIS) of nanotubes.
[0058] Fig.28 This is the SEM image of the single nitrogen source doped melamine precursor prepared in comparative example 3.
[0059] Fig.29 gC prepared in Comparative Example 3 3 N 4 SEM image of nanotubes.
[0060] Fig.30 gC prepared in Comparative Example 3 3 N 4 EDS element distribution diagram of nanotubes (the percentages in the figure are the mass percentages of the corresponding elements). DETAILED DESCRIPTION
[0061] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0062] The raw materials used in the following text are all commercially available. For example, melamine was purchased from the official website of Aladdin Reagent (https: / / www.aladdin-e.com / , CAS No.: 108-78-1).
[0063] Embodiment 1:
[0064] The high nitrogen ratio gC of the present invention 3 N 4 The method for preparing a nanotube array specifically comprises the following steps:
[0065] In the first step, 1.43 g of urea was uniformly dissolved in 50 mL of ultrapure water to form a single nitrogen source mixed solution;
[0066] In the second step, 2 g of hydroxylamine sulfate is added to the mixed solution, and ultrasonically uniformly dissolved to further form a multi-nitrogen source mixed solution; the mass ratio of hydroxylamine sulfate in this step to the volume of ultrapure water in the first step is 0.04 g / mL;
[0067] The third step is to add 1 g of melamine to the above-mentioned multi-nitrogen source mixed solution and perform ultrasonic treatment for 30 minutes to further form a milky white suspension dispersion of the multi-nitrogen source mixed melamine system;
[0068] Step 4: transfer the milky white suspension dispersion into a stainless steel reactor containing 100 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven for hydrothermal reaction at 150°C for 24 hours;
[0069] The fifth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it with ultrapure water and anhydrous ethanol alternately to remove unreacted and water-soluble impurities, and wash it by centrifugation for 7 times, and use ultrapure water for the last time. The purified product is then vacuum dried at 60°C for 24 hours to obtain a multi-nitrogen source doped melamine modified intermediate white powder (i.e., a multi-nitrogen source doped melamine precursor powder, whose microstructure is a nano-columnar array structure, such as Figure 2 shown);
[0070] In the sixth step, 3 g of the multi-nitrogen source-doped melamine-modified intermediate powder is placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. Then, the crucible is placed in a muffle furnace, and the temperature is increased from room temperature to 520°C at a heating rate of 2°C / min in an air atmosphere, and the temperature is further kept for 4 hours for calcination. After calcination, the melamine-modified intermediate powder is naturally cooled to room temperature to obtain a yellow, high nitrogen ratio gC 3 N 4 Nanotube array nanomaterial powder.
[0071] Figure 5 The high nitrogen ratio gC prepared in this example 3 N 4 SEM image of nanotube array.
[0072] Embodiment 2:
[0073] The high nitrogen ratio gC of the present invention 3 N 4 The method for preparing a nanotube array specifically comprises the following steps:
[0074] In the first step, 4.28 g of urea was uniformly dissolved in 100 mL of ultrapure water to form a single nitrogen source mixed solution;
[0075] In the second step, 6 g of hydroxylamine sulfate is added to the mixed solution, and ultrasonically uniformly dissolved to further form a multi-nitrogen source mixed solution; the mass ratio of hydroxylamine sulfate in this step to the volume of ultrapure water used in the first step is 0.06 g / mL;
[0076] The third step is to add 3 g of melamine to the above-mentioned multi-nitrogen source mixed solution and perform ultrasonic treatment for 60 minutes to further form a milky white suspension dispersion of the multi-nitrogen source mixed melamine system;
[0077] Step 4: transfer the milky white suspension dispersion into a stainless steel reactor containing 150 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven for hydrothermal reaction at 200°C for 48 hours;
[0078] The fifth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it with ultrapure water and anhydrous ethanol alternately to remove unreacted and water-soluble impurities, and centrifuge for 7 cycles and use ultrapure water for the last time. The purified product is then vacuum dried at 80°C for 30 hours to obtain a multi-nitrogen source doped melamine modified intermediate white powder (i.e., a multi-nitrogen source doped melamine precursor powder, whose microstructure is a nano-columnar array structure, such as Fig.18 shown);
[0079] In the sixth step, 9 g of the multi-nitrogen source-doped melamine-modified intermediate powder is placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. Then, the crucible is placed in a muffle furnace, and the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min in an air atmosphere, and the temperature is further kept for 5 hours for calcination. After calcination, the melamine-modified intermediate powder is naturally cooled to room temperature to obtain a yellow, high nitrogen ratio gC 3 N 4 Nanotube array nanomaterial powder.
[0080] Fig.19 The high nitrogen ratio gC prepared in this example 3 N 4 SEM image of nanotube array.
[0081] Embodiment 3:
[0082] The high nitrogen ratio gC of the present invention 3 N 4 The method for preparing a nanotube array specifically comprises the following steps:
[0083] In the first step, 2.86 g of urea was uniformly dissolved in 70 mL of ultrapure water to form a single nitrogen source mixed solution;
[0084] In the second step, 4 g of hydroxylamine sulfate is added to the mixed solution, and ultrasonically uniformly dissolved to further form a multi-nitrogen source mixed solution; the mass ratio of hydroxylamine sulfate in this step to the volume of ultrapure water used in the first step is (4 / 70) g / mL;
[0085] The third step is to add 2 g of melamine to the above-mentioned multi-nitrogen source mixed solution and perform ultrasonic treatment for 40 minutes to further form a milky white suspension dispersion of the multi-nitrogen source mixed melamine system;
[0086] Step 4: transfer the milky white suspension dispersion into a stainless steel reactor containing 100 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven for hydrothermal reaction at 180°C for 36 hours;
[0087] The fifth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it repeatedly with ultrapure water and anhydrous ethanol to remove unreacted and water-soluble impurities, and centrifuge for 7 times and use ultrapure water for the last time. The purified product is then vacuum dried at 70°C for 26 hours to obtain a multi-nitrogen source doped melamine modified intermediate white powder (i.e., a multi-nitrogen source doped melamine precursor powder, whose microstructure is a nano-columnar array structure, such as Fig. 20 shown);
[0088] In the sixth step, 6 g of the multi-nitrogen source-doped melamine-modified intermediate powder is placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. Then, the crucible is placed in a muffle furnace, and the temperature is increased from room temperature to 550°C at a heating rate of 5°C / min in an air atmosphere, and the temperature is further kept for 5 hours for calcination. After calcination, the melamine-modified intermediate powder is naturally cooled to room temperature to obtain a yellow, high nitrogen ratio gC 3 N 4 Nanotube array nanomaterial powder.
[0089] Fig.21 The high nitrogen ratio gC prepared in this example 3 N 4 SEM image of nanotube array.
[0090] Embodiment 4:
[0091] The high nitrogen ratio gC of the present invention 3 N 4 The method for preparing a nanotube array specifically comprises the following steps:
[0092] In the first step, 0.74 g of urea was uniformly dissolved in 30 mL of ultrapure water to form a single nitrogen source mixed solution;
[0093] In the second step, 1 g of hydroxylamine sulfate is added to the mixed solution, and ultrasonically uniformly dissolves the mixed solution to further form a multi-nitrogen source mixed solution; the mass ratio of hydroxylamine sulfate in this step to the volume of ultrapure water in the first step is (1 / 30) g / mL;
[0094] The third step is to add 0.5 g of melamine to the above-mentioned multi-nitrogen source mixed solution and perform ultrasonic treatment for 20 minutes to further form a milky white suspension dispersion of the multi-nitrogen source mixed melamine system;
[0095] Step 4: Transfer the milky white suspension dispersion to a stainless steel reactor containing 50 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven at 120° C. for hydrothermal reaction for 12 h;
[0096] The fifth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it with ultrapure water and anhydrous ethanol alternately to remove unreacted and water-soluble impurities, and centrifuge for 7 cycles and use ultrapure water for the last time. The purified product is then vacuum dried at 50°C for 20 hours to obtain a multi-nitrogen source doped melamine modified intermediate white powder (i.e., a multi-nitrogen source doped melamine precursor powder, whose microstructure is a nano-columnar array structure, such as Fig. 22 shown);
[0097] In the sixth step, 1.5 g of the multi-nitrogen source-doped melamine-modified intermediate powder is placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. Then, the crucible is placed in a muffle furnace, and the temperature is increased from room temperature to 500°C at a heating rate of 1°C / min in an air atmosphere, and the temperature is further kept for 3 hours for calcination. After calcination, the melamine-modified intermediate powder is naturally cooled to room temperature to obtain a yellow, high nitrogen ratio gC 3 N 4 Nanotube array nanomaterial powder.
[0098] Fig.23 The high nitrogen ratio gC prepared in this example 3 N 4 SEM image of nanotube array.
[0099] Comparative Example 1:
[0100] The bulk phase gC 3 N 4 The material and the preparation method specifically include the following steps:
[0101] In the first step, 10 g of melamine powder was placed in an alumina crucible with a lid and tightly wrapped with aluminum foil;
[0102] In the second step, the mixture was placed in a muffle furnace, heated from room temperature to 550°C at a heating rate of 10°C / min in an air atmosphere, and further kept at this temperature for 4 hours for calcination. After calcination, the mixture was naturally cooled to room temperature to obtain a yellow, bulk gC 3 N 4 powder.
[0103] Figure 4 , Figure 7 , Fig.11 The "body phase" 3 N 4 "curve, Fig.13 The "body phase" 3 N 4 "curve, Fig.14 , Fig.17 The "body phase" 3 N 4 The curve is the bulk gC prepared in Comparative Example 1.3 N 4 SEM, EDS element distribution, XRD, FT-IR, BET, and UV-Vis diagrams.
[0104] Comparative Example 2
[0105] This comparative example does not use hydroxylamine sulfate, and the prepared product is a dispersed gC 3 N 4 The preparation method of the nanotubes specifically comprises the following steps:
[0106] In the first step, 1.43 g of urea was uniformly dissolved in 50 mL of ultrapure water to form a single nitrogen source mixed solution;
[0107] In the second step, 1 g of melamine is added to the above single nitrogen source mixed solution and ultrasonicated for 30 minutes to further form a milky white suspension dispersion of the single nitrogen source mixed melamine system;
[0108] The third step is to transfer the milky white suspension dispersion into a stainless steel reactor containing 100 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven for hydrothermal reaction at 150°C for 24 hours;
[0109] The fourth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it with ultrapure water and anhydrous ethanol alternately to remove unreacted and water-soluble impurities, and centrifuge for 7 times and use ultrapure water for the last time. The purified product is then vacuum dried at 60°C for 24h to obtain a single nitrogen source doped melamine modified intermediate white powder (i.e., a single nitrogen source doped melamine precursor powder, whose microstructure is a nanocolumn structure, such as Fig.24 shown);
[0110] Step 6: 3 g of the single nitrogen source-doped melamine-modified intermediate powder was placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. The crucible was then placed in a muffle furnace, heated from room temperature to 520 °C at a heating rate of 2 °C / min in an air atmosphere, and further kept warm for 4 h for calcination. After calcination, the yellow gC was obtained after naturally cooling to room temperature. 3 N 4 Nanotube nanomaterial powder.
[0111] Figure 8 , Fig.11 "gC 3 N 4 Nanotube” curve, Fig.13 "gC 3 N 4 Nanotube” curve, Fig.15 , Fig.17 "gC 3 N 4 Nanotube" curve and Fig.25 The EDS element distribution, XRD, FT-IR, BET, UV-Vis and SEM images of the product of Comparative Example 2 are shown.
[0112] Comparative Example 3
[0113] In this comparative example, hydroxylamine sulfate is not used, but the amount of urea is increased, and the gC prepared is a "nanosheet-nanotube-nanosheet" intercalation structure. 3 N 4 The preparation method of the nanotubes specifically comprises the following steps:
[0114] In the first step, 4.28 g of urea was uniformly dissolved in 50 mL of ultrapure water to form a single nitrogen source mixed solution;
[0115] In the second step, 1 g of melamine is added to the above single nitrogen source mixed solution and ultrasonicated for 30 minutes to further form a milky white suspension dispersion of the single nitrogen source mixed melamine system;
[0116] The third step is to transfer the milky white suspension dispersion into a stainless steel reactor containing 100 mL of polytetrafluoroethylene lining, and place it in a constant temperature forced air drying oven for hydrothermal reaction at 150°C for 24 hours;
[0117] The fourth step is to take out the white product in the inner tank after the reactor is cooled to room temperature and wash it with ultrapure water and anhydrous ethanol alternately to remove unreacted and water-soluble impurities, and centrifuge for 7 times and use ultrapure water for the last time. The purified product is then vacuum dried at 60°C for 24h to obtain a single nitrogen source doped melamine modified intermediate white powder (i.e., a single nitrogen source doped melamine precursor powder, whose microstructure is a nanocolumn structure, such as Fig.28 shown);
[0118] Step 6: 3 g of the single nitrogen source-doped melamine-modified intermediate powder was placed in an alumina crucible with a lid, and tightly wrapped with aluminum foil. The crucible was then placed in a muffle furnace, heated from room temperature to 520 °C at a heating rate of 2 °C / min in an air atmosphere, and further kept warm for 4 h for calcination. After calcination, the yellow gC was obtained after naturally cooling to room temperature. 3 N 4 Nanotube nanomaterial powder.
[0119] Fig.29 , Fig.30 The SEM image and EDS element distribution of the product of Comparative Example 3 are shown below.
[0120] Figure 1 This is a scanning electron microscope (SEM) image of the melamine used in Example 1. The image shows that the melamine presents a granular distribution with irregular size and arrangement from a microscopic perspective.
[0121] Figure 2 This is a SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 1. The image shows that after hydrothermal treatment, urea molecules, hydroxylamine sulfate molecules and melamine molecules promote the growth of randomly arranged melamine particles into a nanocolumn array with a directional arrangement structure through supramolecular self-assembly reaction.
[0122] Figure 3 The high nitrogen ratio gC prepared in Example 1 3 N 4 X-ray diffraction (XRD) diagram of multi-nitrogen source doped melamine precursor and melamine of nanotube array. The figure shows that the diffraction peak position of the multi-nitrogen source doped melamine precursor formed by hydrothermal doping of melamine with urea molecules and hydroxylamine sulfate molecules has changed significantly, among which the diffraction peaks at 10.6° and 28.2° of the (100) and (002) crystal planes in the multi-nitrogen source doped melamine precursor correspond to the in-plane stacking and interlayer stacking sequence structures, respectively. This shows that during the hydrothermal process, the melamine molecules further improve the chemical structure of melamine through supramolecular self-assembly reaction and fundamentally transform into a multi-nitrogen source doped melamine precursor.
[0123] Figure 4 The bulk gC prepared by one-step pyrolysis of melamine without any nitrogen source doping as compared with Comparative Example 1 3 N 4 The SEM image shows that after calcination, the irregular melamine particles are transformed into an unevenly dispersed block structure.
[0124] Figure 5 The high nitrogen ratio gC prepared in Example 1 3 N 4 SEM image of nanotube array. The image shows that after the multi-nitrogen source doped melamine precursor is pyrolyzed at high temperature, the hydrogen bonds in the original nanocolumn array structure are partially destroyed, and the inside of the nanocolumn is peeled off, further forming a slightly fluffy high nitrogen ratio gC 3 N 4 Nanotube arrays with an average tube length >30 μm.
[0125] Figure 6 The high nitrogen ratio gC prepared in Example 1 3 N 4 The diameter distribution of the nanotube array. The figure shows that after fitting the high nitrogen ratio gC 3 N 4 The average diameter of the nanotube array is 376.23 nm.
[0126] Figure 7 The bulk phase gC prepared by one-step pyrolysis of melamine in Comparative Example 1 3 N4 Energy dispersive spectrometer (EDS) element distribution diagram. The figure shows that the bulk phase gC 3 N 4 The element distribution includes three categories: carbon (49.54%), nitrogen (44.81%), and oxygen (5.65%).
[0127] Figure 8 The single nitrogen source doped gC prepared in Comparative Example 2 3 N 4 EDS element distribution of nanotubes. The figure shows that single nitrogen source doped gC 3 N 4 The element distribution of the nanotubes includes three categories: carbon (44.62%), nitrogen (52.76%), and oxygen (2.62%).
[0128] Fig. 9 The high nitrogen ratio gC prepared in Example 1 is shown 3 N 4 EDS element distribution of nanotube array. The figure shows that the high nitrogen ratio gC 3 N 4 The element distribution of the nanotube array includes carbon (6.39%), nitrogen (76.59%), and oxygen (17.02%). 3 N 4 and gC 3 N 4 Nanotubes can find high nitrogen ratio gC 3 N 4 The nitrogen content of the nanotube array increased by 1.71 times and 1.45 times respectively.
[0129] Fig.10 The high nitrogen ratio gC prepared in Example 1 3 N 4 Transmission electron microscopy (TEM) image of nanotube arrays. The image shows that the high nitrogen ratio gC 3 N 4 The nanotube array is composed of three-channel nanotubes with hollow interiors.
[0130] Fig.11 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC obtained in Comparative Example 2 3 N 4 XRD comparison of nanotubes. The figure shows that the high nitrogen ratio gC 3 N 4 The nanotube arrays show two characteristic peaks at 13.0° and 27.0°, corresponding to the bulk phase gC3 N 4 Structure and gC 3 N 4 nanotubes, which can be attributed to the interlayer stacking of tri-s-triazine units on the (100) crystal plane and the interlayer stacking of conjugated aromatic units on the (002) crystal plane. However, due to the high nitrogen ratio gC 3 N 4 The formation of hollow nanotube structures in the nanotube array structure and the reduction in the planar size of the interlayer structural units that hinder electron transfer lead to the disappearance of the (100) crystal plane and the weakening of the (002) crystal plane strength.
[0131] Fig.12 The high nitrogen ratio gC prepared in Example 1 3 N 4 The yield graph of nanotube arrays. The graph shows that the preparation method of Example 1 was repeated for multiple experiments, and 3g of multi-nitrogen source-doped melamine precursor was taken for 5 times and then pyrolyzed at high temperature in air atmosphere to form a high nitrogen ratio gC 3 N 4 The average mass of the nanotube array products was 1.5 g, and the yield was about 50%.
[0132] Fig.13 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC obtained in Comparative Example 2 3 N 4 Fourier transform infrared spectra (FT-IR) comparison of nanotubes. The figure shows that the high nitrogen ratio gC 3 N 4 Nanotube arrays and bulk gC 3 N 4 and gC 3 N 4 The nanotubes retain the same chemical structure. 810cm –1 The absorption peak at 1200-1650cm corresponds to the plane bending vibration mode of the tri-s-triazine unit. –1 The absorption peaks in the range 3000-3500cm correspond to the typical stretching vibration modes of the heptazine heterocyclic unit. –1 The multiple absorption peaks in the range are attributed to -NH x Groups and surface-bound H 2 Stretching vibration mode of O molecule.
[0133] Fig.14 The bulk phase gC prepared in Comparative Example 1 3 N 4The specific surface area test (BET) diagram shows that the bulk phase gC 3 N 4 The specific surface area is about 9.8081m 2 / g, and the pore size is about 5 to 25 nm.
[0134] Fig.15 The gC prepared in Comparative Example 2 3 N 4 BET diagram of nanotubes. The figure shows that single nitrogen source doped gC 3 N 4 The specific surface area of the nanotubes is about 11.7449 m 2 / g, and the pore size is about 5 to 25 nm.
[0135] Fig.16 The high nitrogen ratio gC prepared in Example 1 3 N 4 BET diagram of nanotube array. The figure shows that the high nitrogen ratio gC 3 N 4 The specific surface area of the nanotube array is about 36.6938 m 2 / g, compared with bulk gC 3 N 4 and gC 3 N 4 Compared with nanotubes, the pore size is increased by 3.74 times and 3.12 times, respectively, and the pore size is about 5 to 15 nm. This shows that the higher specific surface area can provide more active sites for a wide range of applications such as catalysis, sensing and adsorption.
[0136] Fig.17 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC obtained in Comparative Example 2 3 N 4 The UV-Vis spectrophotometer (UV-Vis) comparison of nanotubes. The figure shows the comparison of bulk phase gC 3 N 4 and gC 3 N 4 Nanotubes, high nitrogen ratio gC doped by multiple nitrogen sources 3 N 4 The absorption edge of the nanotube array expanded from 475nm and 492nm to 508nm. At the same time, the band gap structure decreased from 2.72eV and 2.67eV to 2.60eV (e.g. Fig.17 This indicates that further doping regulation can adjust the high nitrogen ratio gC 3 N 4Nanotube arrays can improve their electronic band structure and expand the scope of application.
[0137] Fig.18 This is a SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 2. The image shows that after hydrothermal treatment, urea molecules, hydroxylamine sulfate molecules and melamine molecules promote the growth of randomly arranged melamine particles into a nanocolumn array with a directional arrangement structure through supramolecular self-assembly reaction.
[0138] Fig.19 The high nitrogen ratio gC prepared in Example 2 3 N 4 SEM image of nanotube array. The image shows that after the multi-nitrogen source doped melamine precursor is pyrolyzed at high temperature, the hydrogen bonds in the original nanocolumn array structure are partially destroyed, and the inside of the nanocolumn is peeled off, further forming a slightly fluffy high nitrogen ratio gC 3 N 4 Nanotube arrays.
[0139] Fig. 20 This is a SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 3. The image shows that after hydrothermal treatment, urea molecules, hydroxylamine sulfate molecules and melamine molecules promote the growth of randomly arranged melamine particles into a nanocolumn array with a directional arrangement structure through supramolecular self-assembly reaction.
[0140] Fig.21 The high nitrogen ratio gC prepared in Example 3 3 N 4 SEM image of nanotube array. The image shows that after the multi-nitrogen source doped melamine precursor is pyrolyzed at high temperature, the hydrogen bonds in the original nanocolumn array structure are partially destroyed, and the inside of the nanocolumn is peeled off, further forming a slightly fluffy high nitrogen ratio gC 3 N 4 Nanotube arrays.
[0141] Fig. 22 This is a SEM image of the multi-nitrogen source doped melamine precursor prepared in Example 4. The image shows that after hydrothermal treatment, urea molecules, hydroxylamine sulfate molecules and melamine molecules promote the growth of randomly arranged melamine particles into a nanocolumn array with a directional arrangement structure through supramolecular self-assembly reaction.
[0142] Fig.23 The high nitrogen ratio gC prepared in Example 4 3 N 4 SEM image of nanotube array. The image shows that after the multi-nitrogen source doped melamine precursor is pyrolyzed at high temperature, the hydrogen bonds in the original nanocolumn array structure are partially destroyed, and the inside of the nanocolumn is peeled off, further forming a slightly fluffy high nitrogen ratio gC3 N 4 Nanotube arrays.
[0143] Fig.24 This is a SEM image of the single nitrogen source doped melamine precursor prepared in Comparative Example 2. The image shows that after hydrothermal treatment, urea molecules and melamine molecules promote the in-situ formation of a nano-columnar structure of randomly arranged melamine particles through supramolecular self-assembly reaction, and the arrangement is relatively disordered.
[0144] Fig.25 gC prepared in Comparative Example 2 3 N 4 SEM image of nanotubes. The image shows that after the single nitrogen source doped melamine precursor is pyrolyzed at high temperature, the original nanocolumn structure is peeled off inside and further forms a nanotube structure in situ. Among them, the more dispersed nanotubes have slightly lower conductivity, smaller specific surface area, and fewer limited active sites than the regular and ordered nanotube arrays.
[0145] Fig.26 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC prepared in Comparative Example 2 3 N 4 Comparison of cyclic voltammetry (CV) of nanotubes in 5mM potassium ferrocyanide / potassium ferrocyanide and 0.1M potassium chloride solution. 3 N 4 The oxidation peak and reduction peak currents (84.8 μA, -80.0 μA) of the nanotube array were significantly higher than those of gC 3 N 4 Nanotubes (72.0μA, -67.9μA) and bulk gC 3 N 4 (50.8μA, -49.0μA).
[0146] Fig. 27 The high nitrogen ratio gC prepared in Example 1 3 N 4 Nanotube array and bulk phase gC obtained in Comparative Example 1 3 N 4 And the gC prepared in Comparative Example 2 3 N 4 Comparison of electrochemical impedance spectroscopy (EIS) of nanotubes in 5mM potassium ferrocyanide / potassium ferrocyanide and 0.1M potassium chloride solution. 3 N 4The charge transfer resistance (Rct) of the nanotube array (1034Ω) is significantly lower than that of gC 3 N 4 Nanotubes (1494Ω) and bulk gC 3 N 4 (1959Ω).
[0147] Fig.28 This is a SEM image of the single nitrogen source doped melamine precursor prepared in Comparative Example 3. The image shows that after hydrothermal treatment, urea molecules and melamine molecules promote the in-situ formation of staggered nano-columnar structures of randomly arranged melamine particles through supramolecular self-assembly reaction.
[0148] Fig.29 gC prepared in Comparative Example 3 3 N 4 SEM image of nanotubes. The image shows that after the single nitrogen source doped melamine precursor is pyrolyzed at high temperature, the original nanocolumn structure is peeled off to form an independent sheet structure. As the calcination time increases, the peeling layer of the intermediate is transformed into nanotubes through self-curling, forming an intercalation structure of "nanosheet-nanotube-nanosheet" as a whole. Among them, due to the tight intercalation structure, compared with the regular and ordered nanotube array, the specific surface area provided is smaller and the limited active sites are also fewer.
[0149] Fig.30 The single nitrogen source doped gC prepared in Comparative Example 3 3 N 4 EDS element distribution of nanotubes. The figure shows that single nitrogen source doped gC 3 N 4 The element distribution of the nanotubes includes three categories: carbon (38.21%), nitrogen (60.06%), and oxygen (1.73%). The nitrogen content is significantly lower than that of the product in Example 1. It can be seen that when only urea is used as a nitrogen source, even if the amount of urea is further increased, the nitrogen content of the final product is not significantly increased (Comparative Examples 2 and 3 both use only urea as a nitrogen source, and the amount of urea in Comparative Example 3 is 3 times that of Comparative Example 2, but the nitrogen content of the product is only increased from 52.76% to 60.06%, which is not as significant as the nitrogen content of the product in Example 1, which is 76.59%).
[0150] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a g-C3N4 nanotube array with a high nitrogen ratio, characterized in that: The following steps are involved: (1) uniformly dissolving urea in water to obtain a single nitrogen source mixed solution; (2) adding hydroxylamine sulfate to the single nitrogen source mixed solution and uniformly dissolving it to obtain a multi-nitrogen source mixed solution; (3) adding melamine to the multi-nitrogen source mixed solution, mixing and dispersing the mixture uniformly to obtain a dispersion of a multi-nitrogen source mixed melamine system; (4) subjecting the dispersion of the multi-nitrogen source mixed melamine system to a hydrothermal reaction, wherein the hydrothermal temperature of the hydrothermal reaction is 120° C.-200° C., and the reaction time is 12 h-48 h; after the reaction is completed, collecting the reaction product, and washing and drying the reaction product to obtain a multi-nitrogen source doped melamine precursor powder; the multi-nitrogen source doped melamine precursor powder has a nano columnar array structure; (5) The multi-nitrogen source doped melamine precursor powder is tightly wrapped with aluminum foil and then calcined in an air atmosphere to obtain a g-C3N4 nanotube array nanomaterial with a high nitrogen ratio.
2. The preparation method according to claim 1, characterized in that: The usage ratio of the urea, the hydroxylamine sulfate and the melamine satisfies the mass ratio of (0.74g-4.28g):(1g-6g):(0.5g-3g).
3. The preparation method according to claim 1, characterized in that: In the multi-nitrogen source mixed solution, the ratio of the mass of the hydroxylamine sulfate to the volume of the solvent water is (1 / 30) to 0.06 g / mL.
4. The preparation method according to claim 1, characterized in that: In step (3), the dispersion is carried out by ultrasonic treatment, and the ultrasonic treatment time is 20-60 minutes.
5. The preparation method according to claim 1, characterized in that: In step (4), the cleaning is specifically performed by using ultrapure water and ethanol for multiple alternating cleanings; the drying temperature used in the drying is 50° C.-80° C., and the drying time is 20 h-30 h.
6. The preparation method according to claim 5, characterized in that: In step (4), the cleaning is specifically carried out by alternating ultrapure water and ethanol for a total of 7 times, and the last time is ultrapure water.
7. The preparation method according to claim 1, characterized in that: In step (5), the calcination temperature is 500°C-600°C, the heating rate is 1°C / min-10°C / min, and the holding time is 3h-5h.
8. A g-C3N4 nanotube array with a high nitrogen ratio obtained by the preparation method as described in any one of claims 1 to 7.
9. The high nitrogen ratio g-C3N4 nanotube array according to claim 8, characterized in that: The mass percentage of nitrogen element in the high nitrogen ratio g-C3N4 nanotube array is greater than 44.81%, preferably greater than 52.76%.
10. The high nitrogen ratio g-C3N4 nanotube array according to claim 8, characterized in that: In the high nitrogen ratio g-C3N4 nanotube array, the elemental mass percentages of carbon, nitrogen, and oxygen are 17.02%, 76.59%, and 6.39%, respectively.
Citation Information
Cited By
High-yield nitrogen-doped g-C3N4 micron tube and preparation method thereof
CN121894622A